Review of Sargassum thunbergii (Fucales, Phaeophyta): phycology, chemistry, bioactivity, and application - Xueyu Wang; Dandan Xiao; In-Kyu Yeo; Lei Wang; Yiqiao Li; Jia Fu; Yunhua Fu; Suengmok Cho; You-Jin Jeon; Fengqi Yang (Algae, 2025)
Sargassum thunbergii is a large brown seaweed endemic to the Northwest of Pacific Ocean, widely distributed in the warm temperate coastal waters of South Korea, China, and Japan. It is abundant in resources and has a long history of application, widely used in food, medicine, and feed. In recent years, it has also been used to restore marine ecology. To date, only one review has been published on Sargassum thunbergii aquaculture. Therefore, by investigating the international definitive data repository (ScienceDirect, PubMed, Web of Science, ACS Publications, Springer, etc.) and collecting 92 kinds of literature closely related to phycology, chemistry, biological activity, and applications, herewith a comprehensive and systematic summary and exposition, enveloping the classification and distribution, botanical characteristics, and physiological and biochemical differences of Sargassum thunbergii ; involving 7 chemical classifications of 117 derivatives substances embracing 12 new and 6 first-isolated excluding polysaccharides; mainly including 11 types of pharmacology in vivo and in vitro; evaluating the potential applications related on medicine, healthcare, aquaculture, and marine restoration. This review is expected to provide forward-looking scientific perspectives and act as a valuable reference for future studies, development, and utilization of Sargassum thunbergii .